Estresse em discentes de enfermagem de quatro instituições brasileiras - Bublitz, Susan (2014)
This study aimed to verify the level of stress in nursing students from four Brazilian institutions. It is a cross-sectional and descriptive study with quantitative approach developed with 705 nursing undergraduate students from four Brazilian Education Institutions being three of them from the southeast region and one from the southern. The data were collected between April 2011 and March 2012 according to the chronogram of each institution, after signing of the free and informed consent term through a research protocol that included: Sociodemographic and Form of Academic and Learners Instrument Rating Stress in Nursing Students (EEAA). After the data collection were performed a database in Excel spreadsheet for Windows program and they were analyzed by the software Statistical Analysis System (SAS - version 9.02) and Statistical Package for Social Sciences (SPSS version 16). There was a predominance of female students (84.54 %), with age between 20 and 24 years (50 %), single (76.88 %) and without children (83.12 %). Among the students with children, the majority had one child (58.82 %). 76.42 % live with relatives. It was found that 75.64 % do not practice sports and 60.53 % practice leisure activities. About the academic characteristics 71.73 % do not participate in research/study group and 72.40 % do not receive academic scholarships. However among those who receive financial aid scholarship, the predominant type is in the assistance activities (45.08 %).The most students do not develop any work activity (74.25%), and do not have any university grade (96.88 %). 89.84% of the students said to be satisfied with the course and 36.79% have thought about giving up on it. About the level of stress was observed 15.10% of nursing students are in high stress level, 74.47% in medium level and 9.93 % in the low stress level. In the domains analysis who that had a higher percentage of students in high stress level was Time Management (31.77%). Based on the average of items that make up the EEAA the situation of increased stress for nursing students was having concern about their professional future (x= 2,16). Relating the stress with the sociodemographic and academic characteristics of nursing students, it was found difference statistically significant of the stress with the following variables: age, institution type (public / private), work activity, satisfaction with the course and ever thought about giving up on it. In this sense to know the characteristics of nursing students and stress level of the same, as well as stressors in the academic environment can contribute to propose measures to minimize the effects among these individuals because minimizing the stress is expect better academic performance, less wear and greater satisfaction into of the labor world, since the situations experienced during the academic training are similar to the professional future.